The contribution of the systemic inflammatory response to the outcome of spinal cord injury - Yates, AG (2021)
Non-resolving inflammation in the spinal cord following traumatic injury causes the progressive destruction of neuronal tissue, which exacerbates functional deficits. However, therapy targeting inflammation within the spinal cord has, to date, generated equivocal results, and there remains no clinically approved pharmacological intervention for spinal cord injury (SCI). Therefore, there is an immediate need to identify novel therapeutic targets. Traumatic central nervous system injuries, including SCI, induce near-immediate peripheral inflammation, which is described as the acute phase response (APR). Previous studies have shown that suppression of the APR can attenuate leukocyte infiltration and associated secondary damage in models of brain injury. In light of these results, it was my hypothesis that there would be a direct relationship between the magnitude of the APR and the spinal cord injury pathology, and also that therapeutic manipulation of this response would lead to improved outcomes. This was tested in a mouse contusion model of SCI, which allowed for controlled variation of both the severity and level of injury. Following injury, the systemic response was characterised throughout the first 24 hours. The studies described herein indicate that SCI induces a robust APR, as evidenced by the increased hepatic expression of pro-inflammatory mediators, leukocyte mobilisation into the blood, and also recruitment to the liver and spleen. The magnitude of this response was dependent on the severity and level of injury, but the relationship was more complex than anticipated. Importantly, the APR preceded leukocyte infiltration to the spinal cord and, for this reason, a not previously recognised “therapeutic window” appears to exist. Here, a rapid increase in IL-1β expression within the liver was found to be a prominent feature of SCI that preceded the expression of the endogenous antagonist IL-1RA. IL-1RA was administered to rectify the early mismatch in expression, and, as a consequence, inflammation in the spinal cord was reduced. Further exploration of the systemic response to SCI revealed metabolite changes in peripheral tissues that were predictive of patient outcome. In mice, the acute metabolite changes were similar in sham and spinal cord injured mice but, at later time points, the SCI had an impact on the peripheral metabolome that was distinct from the changes induced by a sham operation. Normalisation of these changes might be expected to prevent some of the downstream peripheral sequelae associated with SCI. The role of extracellular vesicles (EVs) as possible mediators of the APR was also explored. Plasma EVs were significantly increased two hours post-SCI, and EVs, isolated from donor SCI animals, were able to alter the hepatic expression profile of inflammatory genes in vivo in recipient animals. These results suggest that circulating EVs after SCI may serve to regulate the APR. Collectively, the data presented in this thesis show that SCI induces significant systemic changes that are dependent on the nature of the lesion and appear to influence the penultimate outcome. Manipulation of the APR in the first 24 hours after an SCI is a very accessible and mostly overlooked target for therapeutic intervention. IL-1RA treatment was already shown to be an effective therapy here, but my studies also highlight the abnormal expression of other cytokines by the liver, which could also be additionally targeted. It is shown that manipulation of circulating EV populations or the peripheral metabolome might otherwise also prove beneficial after SCI.